Determining and Measuring Self-Efficacy During the Student Teaching Semester - Carolyn Fehrenbach; Kenny Mc Dougle; Steve Brown; Ray Willard; Pam Sells; Charles Kent Runyan (The Advocate, 2014)
Self-efficacy is the belief that an individual is able to control the outcomes of potentially stressful situations. How teacher candidates feel about their ability to control new challenges can affect their performance in the classroom. Those with a poorer sense of self-efficacy may believe situations are out of their control. A more positive sense of perceived self-efficacy can lead to more positive outcomes. This article reports the results of a teacher self-efficacy scale administered to elementary and secondary teacher candidates at the beginning and end of their student teaching semester. Findings suggest that perceived self-efficacy among student teachers increases throughout the course of the student teaching experience.